Development of a radioimmunoassay (RIA) method for the isolation, determination and quantification of stilbene residues (DES, DIEN, HEX) in tissues - TYRPENOU (Α.Ε.ΤΥΡΠΕΝΟΥ), A. Ε. (Journal of the Hellenic Veterinary Medical Society, 2018)
An accurate, reliable and reproducible radioimmunoassay (RIA) method was developed and evaluated for the isolation, determination and quantification of stilbenes (DEX, DIEN and HEX) in animal tissue. The radioimmunoassay principle, the production of the antiserum, the optimum dilution for binding at 50% and the cross reactivity determination are described. Also, the calculations for the construction of the standard calibration curve and several other specific steps of RIA are included. DES antiserum was raised in rabbits and under the assay conditions its optimum dilution was found to be 1:4000 and the sensitivity of the assay 10 pg/tube. The DES antiserum produced was very specific, with a crossreactivity for oestradiol <0,01% and for hoexestrol less than 9,6%. However, problems were encountered with regard to nonspecific adsorption by charcoal (charcoal blank) during RIA and the reproducibility of the standard curves were overcome by having standards and the assay samples in 20% methanolic: phosphate buffered saline (MeOH:PBS 20%). The recovery of the cleanup step was more than 90% and the recovery of the method was ranged between 65 and 75%. This method has been developed for the analysis of stilbene residues in veal and chicken meat tissue and it is suggested as a basic procedure for the development of other RIA methods for hormone residue determination in food producing animals.